Calderon-Zygmund estimates for higher order systems with p(x) growth - Habermann, Jens (Mathematische Zeitschrift, 2008)
For weak solutions Equation Presented of higher order systems of the type Equation Presented with variable growth exponent p : Ω → (1,∞) we prove that if |F|p(̇) ∈ Lqloc (Ω) with 1 < q < n/n-2 + δ, then |Dmu|p(̇) ∈ ∈ Lqloc (Ω). We should note that we prove this implication both in the non-degenerate (μ > 0) and in the degenerate case (μ = 0). © 2007 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2008.nat.dma.lma2.calder